Wolff-Parkinson-White Syndrome Mimics a Conduction Disease - S. Marrakchi; I. Kammoun; S. Kachboura (Case Reports in Medicine)
Background. It is important to recognise Wolff-Parkinson-White (WPW) syndrome in electrocardiograms (ECG), as it may mimic ischaemic heart disease, ventricular hypertrophy, and bundle branch block. Recognising WPW syndrome allows for risk stratification, the identification of associated conditions, and the institution of appropriate management. Objective. The present case showed that electrophysiological study is indicated in patients with abnormal ECG and syncope. Case Report. A 40-year-old man with Wolff-Parkinson-White syndrome was presented to emergency with syncope. A baseline ECG was a complete right branch block and posterior left hemiblock. He was admitted to the cardiac care unit for pacemaker implantation. The atypical figure of complete right branch block and posterior left hemiblock was thought to be a “false positive” of conduction abnormality. But the long anterograde refractory period of the both accessory pathway and atrioventricular conduction may cause difficulty in diagnosing Wolff-Parkinson-White syndrome, Conclusion. A Wolff-Parkinson-White Syndrome may mimic a conduction disease. No reliable algorithm exists for making an ECG diagnosis of a preexcitation syndrome with conduction disorders. This can lead to diagnostic and therapeutic dilemmas in the context of syncope.